Climate Risk Case Study : Bulleh Shah Paper Mills - Packages, Ltd., Kasur, Pakistan - Stenek, Vladimir; Colley, Michelle; Connell, Richenda; Firth, John (International Finance Corporation, Washington, DC, 2017)
This report presents a climate risk assessment for International Finance Corporation (IFC’s) investment in Bulleh Shah Paper Mills (BSPM) in Kasur, Pakistan. This facility is owned by Packages Limited, the leading integrated paper products manufacturer in Pakistan. Starting in 2005, packages began to relocate its paper manufacturing facilities from Lahore (which has limited capacity for expansion), to Kasur. This has allowed the company to increase paper and paperboard production at the new site, while continuing to operate a packaging production plant at Lahore. This study explores the potential climate risks to the company’s operational and engineering plant, to wheat straw input yields, to groundwater resources, and to the local community. In the absence of detailed information on the company’s sensitivity to climate variability (a site visit was not possible for this case study) this report also presents a general overview of the climate risks faced by the pulp and paper sector worldwide. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.